1999
DOI: 10.1088/0953-8984/11/29/315
|View full text |Cite
|
Sign up to set email alerts
|

Densification of growing coatings by ion beams

Abstract: A theoretical model to describe the evolution of microstructure of thin films and densification by ion assistance is proposed. In the model kinetics of point defects, including their interaction with voids and with the growing film surface, is considered. To solve the set of equations a computer code was developed. Film densification by ion bombardment is investigated as a function of ion energy and the ratio of ion-to-vapour current densities. It is shown that there are optimal ion energy and ratio of ion-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Generally speaking, mild ion bombardment causes densification of plasma polymers, giving way to sputtering as the ion bombardment conditions becomes more severe. 31,47,48 In our studies, postdeposition N 2 plasma treatment at an rf power of 100 W caused the visible fringence patterns of the as-deposited films to diminish and eventually disappear. Subsequent analysis by XPS confirmed that the film had been sputtered away, leaving behind a surface composed primarily of SiO 2 with trace amounts of C, N, and Br.…”
Section: ' Results and Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Generally speaking, mild ion bombardment causes densification of plasma polymers, giving way to sputtering as the ion bombardment conditions becomes more severe. 31,47,48 In our studies, postdeposition N 2 plasma treatment at an rf power of 100 W caused the visible fringence patterns of the as-deposited films to diminish and eventually disappear. Subsequent analysis by XPS confirmed that the film had been sputtered away, leaving behind a surface composed primarily of SiO 2 with trace amounts of C, N, and Br.…”
Section: ' Results and Discussionmentioning
confidence: 57%
“…An alternative hypothesis to explain the delamination behavior of our films focuses on the influence of ion bombardment during deposition. The densification of CVD films subjected to ion bombardment has been studied extensively, and it is possible that the porosity of films deposited in BrCN discharges arises, at least in part, as a result of milder ion bombardment conditions relative to CH 3 CN plasmas. The possibility of milder ion bombardment conditions in BrCN plasmas may be justified based on the presence of electronegative Br.…”
Section: Resultsmentioning
confidence: 99%